Polymerization of ethylene oxide under controlled monomer addition via a mass flow controller for tailor made polyethylene oxides. Issue 24 (24th May 2016) - Vitz, Jürgen; Majdanski, Tobias C.; Meier, Alexander; Lutz, Pierre J.; Schubert, Ulrich S.
Abstract : The synthesis of polymers with controlled molecular and structural parameters is challenging due to the required purity of the chemicals and the exclusion of protic impurities and oxygen in particular in the case of an anionic process as shown here. Abstract : The synthesis of polymers with controlled molecular and structural parameters is challenging due to the required purity of the chemicals and the exclusion of protic impurities and oxygen in particular in the case of an anionic process as shown here. In addition, a pressure build-up in the case of gaseous monomers must be considered as well as other safety requirements regarding explosive and very toxic materials. In the present work, ethylene oxide was used as the monomer and converted to polyethylene oxide (PEO), and subsequently polyethylene glycol (PEG) via the anionic ring opening polymerization technique (AROP). Thereby, different homopolymers with a varying chain length were successfully synthesized with narrow molar mass dispersities ( Đ between 1.03 up to 1.09). An important aspect to mention is that the obtained molar mass of the final products matches nicely with the theoretically calculated values by the application of a customized mass flow controller suitable for liquids and gases. Two of them were recently integrated into the existing equipment together with an automation and control system, enabling the exact and controlled addition of any monomer down to 0.1 g h −1 and up to 200 g h −1, even against higher pressure and at different temperatures. Since the automation can be controlled online, no person has to be present during the monomer addition, which leads to improved safeness for the operator. Together with online monitoring, e.g. with FT-IR or UV/Vis, polymerizations were performed more efficiently and faster to yield, e.g., PEG/PEO, which is nowadays an important polymer used in personal, home and health care applications due to the water solubility of low molar mass PEG/PEO in combination with a very low toxicity (for molar masses above 400 g mol −1 ).